Partitioning and exocytosis of secretory granules during division of PC12 cells - Bukoreshtliev, Nickolay Vassilev; Eichler, Tilo Wolf; Eifart, Patricia; Rustom, Amin; Gerdes, Hans-Hermann (International journal of cell biology, 2012)
The biogenesis, maturation, and exocytosis of secretory granules in interphase cells have been well documented, whereas the distribution and exocytosis of these hormone-storing organelles during cell division have received little attention. By combining ultrastructural analyses and time-lapse microscopy, we here show that, in dividing PC12 cells, the prominent peripheral localization of secretory granules is retained during prophase but clearly reduced during prometaphase, ending up with only few peripherally localized secretory granules in metaphase cells. During anaphase and telophase, secretory granules exhibited a pronounced movement towards the cell midzone and, evidently, their tracks colocalized with spindle microtubules. During cytokinesis, secretory granules were excluded from the midbody and accumulated at the bases of the intercellular bridge. Furthermore, by measuring exocytosis at the single granule level, we showed, that during all stages of cell division, secretory granules were competent for regulated exocytosis. In conclusion, our data shed new light on the complex molecular machinery of secretory granule redistribution during cell division, which facilitates their release from the F-actin-rich cortex and active transport along spindle microtubules.
Gesehen am 14.09.2018